Comparison of total laparoscopic hysterectomy and abdominal hysterectomy; A retrospective study in a tertiary center southeastern Turkey - Erdem, Selami; Ege, Serhat (Annals of Medical Research, 2021)
Aim: This study aimed to compare the morbidities of abdominal and laparoscopic hysterectomies to determine the most appropriate hysterectomy method and to identify possible risks when planning surgery. Material and Methods: The records of 50 patients who underwent abdominal hysterectomy (group 1) and 213 patients who underwent total laparoscopic hysterectomy (group 2) between January 2017 and March 2018 in our obstetrics and gynecology clinic were reviewed retrospectively. Results: In patients included in our study, the analgesic requirement was found to be significantly higher in Group 1 than in Group 2 (4.62±1.41 and 4.02±1.54, respectively). While the mean hospital stays in group 1 was significantly higher than in group 2 (2.56 ± 1.24 days, 2.07 ± 0.76 days, respectively), the mean operation time was higher in group 2 than in group 1 (96.70 ± 40.85 min and 141.29 ± 42.35 min, respectively). The postoperative hematoma and urethral injury is seen in group 2 were significantly higher than group 1 (p=0.04 and p=0.04, respectively).Conclusion: The advantages of laparoscopic hysterectomy were shorter duration of hospitalization and less analgesic needs, while the disadvantage of this method was the longer duration of surgery, greater the risk of urinary system complications, and the need for a turn to laparotomy. Therefore, when planning laparoscopy, peri-operative preparations should be made in terms of long surgical time and management of possible complications.
Keywords: Abdominal hysterectomy; complications; laparoscopic hysterectomy